EVALUATION OF DRAINAGE SYSTEM IN SIMOREJO SETTLEMENT AREA, SIMOMULYO VILLAGE, SUKOMANUNGGAL SUB-DISTRICT, SURABAYA CITY - Satriya, M Gilang Ridwanafriansyah; Saves, Faradlillah (Fakultas Teknik Universitas Tanjungpura, 2023)
Flooding frequently occurs in the Simorejo Settlement Area, Simomulyo Village, Sukomanunggal Sub-District, Surabaya City, Indonesia. Recent flooding revealed that the existing channel's capacity was insufficient to handle flood discharge. Therefore, an evaluation of the drainage channels was carried out to determine design and existing flood discharges and channel re-designing measures. Rain data from 2012 to 2021, for the last decade, was used in the evaluation. Maximum rainfall was calculated using the arithmetic method, while design and existing channel discharges were calculated based on the rational method with a maximum rainfall of 2 years, 5 years, and 10 years. The calculation results showed that the channel condition was unable to accommodate the planned flood discharge with a 2-year, 5-year, and 10-year return period. Consequently, re-designing was carried out using a trial and error method until the channel was able to accommodate the design of flood discharge. The re-designing process resulted in an enlarged drainage channel cross-section with dimensions of 1.2 m x 1 m x 1 m.